FORECASTING THE RUNOFF ON RIVERS OF THE DNISTER RIVER BASIN ACCORDING TO THE REMO NUMERIC CLIMATIC MODEL - Vasyl Grebin (World Science, 2018)
This article presents the results of forecasting of future changes in water runoff in the basin of the Dnister River. The forecast is made until the year 2100 in 30-year periods. For forecasting, the data from the network of hydrological stations at Dnister and its affluents. After conducting the verification (testing) of the selected REMO climatic model, an adjustment coefficient was developed and its use was proposed when forecasting the runoff. The results of the forecast have shown the decrease in the value of the runoff modulus for each of the forecasted periods. The deviation of forecasted runoff rates from the control period (1970-2000) with the use of the coefficient for the period 2011-2040 was (in average for the basin) 0.81 l/s*km2 (9%); for the period 2041-2070 it was 0.96 l/s*km2 (11%); for the period 2071-2100 it was 0.88 l/s*km2 (10%).